Core-Periphery Relations and Organization Studies - Westwood, R.; Jack, G.; Khan, F.; Frenkel, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Core-Periphery Relations and Organization Studies draws together postcolonial and indigenous thinking through the conceptual lens of core-periphery relations to advance debate in organization studies. A particular aim of this book is to broaden, deepen and critically reassert a postcolonial imagination in this domain.
Keywords: Organization; Planning; Management; International business enterprises; Leadership; Behavioral economics; International economics; Organization; Management; International Business; Business Strategy/Leadership.; Behavioral/Experimental Economics; International Economics